New Results for the BBM Equation (Journal of Mathematical Study, 2016)
The BBM equation posed on $\mathbb{R}$ and $\mathbb{R}^+$ is revisited. Improving on earlierresults, global well-posedness and bounds for the growth in time of relevant norms ofsolutions corresponding to very general auxiliary data are derived.
Keywords: BBM equation; local well posedness; global well posedness; quarter plane problem; wave maker problem.